PENENTUAN Cu, Pb, Cd, dan Zn DALAM AIR SECARA STRIPPING POTENTIOMETRI DENGAN ELEKTRODA KONVENSIONAL DAN KOMBINASI - Sahara, E. (Jurnal Kimia (Journal of Chemistry); Vol. 2, No. 2 Juli 2008)
This paper discusses the development of stripping potentiometric methods for reliable determination of Cu, Pb, Cd, and Zn in natural water. The electrode systems used were the conventional and combined ones. The formation of intermetallic compound between Cu and Zn was overcame with the addition of gallium ions. The method involved two stripping cycles during which copper was initially determined on its own, followed by simultaneous determination of Pb, Cd and Zn after addition of 150 mg/L gallium ions. The optimum conditions for reliable determination of the metals with the use of the conventional electrode were 0.01 M HCl, 10 mg/L Hg (II), a deposition potential of -1200 mV and a deposition time of 30 seconds, while those with the use of the combined electrode included 0.01 M HCl, 10 mg/L Hg (II), a deposition potential of -700 mV for Cu and -1300 mV for the other three metals and a deposition time of 10 seconds. It was also found that the use of the combined electrode gave lower detection limit and wider linear concentration range for the four metals.
Keywords: sripping potensiometry, electrode conventional, combined, Cu, Pb, Cd, Zn